Karakteristik Komposit Polimer dengan Matriks Polistirena dan Bahan Pengisi dari Berbagar Limbah Pabrik Kelapa Sawit - Hidayani, Tengku Rachmi; Hutajulu, Poltak Evencus; Marbun, New Vita Mey Destty; Pardede, Erwin; Paramitha, Ratih; Nasution, Reni Silvia (Politeknik ATI Padang, 2024)
The first stage of this research was to make polystyrene grafted with maleic anhydride for making the couping agent with other filling compound. In the second stage, the polystyrene matrix grafted with maleic anhydride was combined with filler material derived from palm oil mill waste using the dry mixing method with an internal mixer. Among several variables tested, the optimum composition of the polymer composite was found to be Polystyrene grafted with maleic anhydride: sludge: boiler ash in a ratio of 60:25:15. This composition exhibited a Young's modulus of 856.752 MPa, a tensile strength of 6.057 MPa, and an elongation at break of 0.775%. Differential Scanning Calorimetry (DSC) testing revealed a glass transition temperature of 403.22°C, a crystallization temperature of 426.39°C, and a cross-linking indication temperature of 478.64°C. Scanning Electron Microscopy (SEM) tests showed an even distribution of the material. Fourier-transform infrared (FT-IR) spectroscopy indicated a decrease in absorption peaks at 3024.94 cm⁻¹ and 3025.15 cm⁻¹, while the polystyrene characteristics at the wave number 1600.57 cm⁻¹ appeared sharper. The sound absorption test results met the ISO 11654:1997 standard for the rating level of sound absorption coefficient in materials, achieving Class D and C sound absorption with an αₙₓ value ranging from 0.328 to 0.793.